1994
DOI: 10.30541/v33i4iipp.663-676
|View full text |Cite
|
Sign up to set email alerts
|

Consanguineous Marriages in Pakistan

Abstract: In societies where marriage is nearly universal, and the fertility process is almost entirely through marital union, the factors associated with the occurrence of marriage, and through it the reproduction and rearing of children, need to be continuously assessed. Except for prohibited relationships, marriages between close and distant relations, as well as between those not related have been practiced among the muslims. The high incidence of close kin marriages (consan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…These results are compatible with the higher rates of consanguinity reported among Pakistani populations than among Indian populations [43,44], and with documented preferences of the Makrani [61] and Balochi [62,63] populations for consanguineous marriage. Interestingly, whereas high levels of consanguinity have been reported among the Hazara in Afghanistan [64,65], F hbd values in the Pakistani Hazara population in our data set are among the lowest observed in Central/South Asians.…”
Section: Resultssupporting
confidence: 88%
“…These results are compatible with the higher rates of consanguinity reported among Pakistani populations than among Indian populations [43,44], and with documented preferences of the Makrani [61] and Balochi [62,63] populations for consanguineous marriage. Interestingly, whereas high levels of consanguinity have been reported among the Hazara in Afghanistan [64,65], F hbd values in the Pakistani Hazara population in our data set are among the lowest observed in Central/South Asians.…”
Section: Resultssupporting
confidence: 88%
“…In Pakistan, higher frequencies of consanguinity have been associated with living in rural areas, lower education, and younger age at marriage [4,6]. Thus, it was expected that the UK-born Pakistanis who have lived primarily in urban areas and generally have higher education than their parents would change their marriage pattern [7].…”
Section: Introductionmentioning
confidence: 99%
“…A large household and obstetric inpatient survey of seven cities in the Punjab province found that 46.8% of marriages were consanguineous, to relatives such as second cousins or closer [12]. Higher frequencies of consanguineous marriage are associated with rural areas, lower levels of education and younger age at marriage, and lower frequencies are associated with urban areas and education, indicating a class dimension to the practice [11, 13]. …”
Section: Introductionmentioning
confidence: 99%